Social construction in plastic waste management for community empowerment and regional structure - Arifin Saleh; Mujahiddin Mujahiddin; Sigit Hardiyanto (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The growth rate of plastic waste in Indonesia increases every year. The Central Statistics Agency (BPS) revealed that plastic waste in Indonesia reaches 66 million tons per year. In Hamlet 15, Pematang Johar Village, there is the Suka Mulia Garbage Bank, which has been established since 2020 and has 60 customers. The presence of this waste bank has changed waste management activities, especially plastic. Villagers have started to actively save waste and turn plastic waste into eco-bricks. Changes in waste management in the community make this research aim to analyze the process of change that occurs by using the social construction approach proposed by Berger and Luckmann. This research design is qualitative with a descriptive approach. The data in this study consisted of secondary and primary data. The results of this study found that there is a social construction model in plastic waste management, where from the externalization stage to the objectification stage, a community empowerment process occurs through the socialization of ideas and practices for making ecobricks.